181k views
5 votes
Algebra 2 help needed!

Algebra 2 help needed!-example-1
User YeenFei
by
5.5k points

1 Answer

4 votes

Answer:

(g + f) (x) = (2^x + x – 3)^1/2

Explanation:

The following data were obtained from the question:

f(x) = 2^x/2

g(x) = √(x – 3)

(g + f) (x) =..?

(g + f) (x) can be obtained as follow:

(g + f) (x) = √(x – 3) + 2^x/2

(g + f) (x) = (x – 3)^1/2 + 2^x/2

(g + f) (x) = (x – 3)^1/2 + (2^x)^1/2

(g + f) (x) = (x – 3 + 2^x)^1/2

Rearrange

(g + f) (x) = (2^x + x – 3)^1/2

User Adam Sh
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.